МЕСHANICAL BEHA VIOR OF GRADED HONEYCOMB AND ITS MULTI-OBJECTIVE OPTIMAL DESIGN - CHEN BiMin; HUANG XiaoDi (Jixie qiangdu)
Gradient honeycombs have received extensive attention due to their excellent mechanical properties and crashworthiness. Taking the crashworthiness index of the honeycomb as the optimization goal, in the design space of the gradient honeycomb, the multi-objective optimization algorithm is directly used to determine the specific parameters of each layer of the gradient honeyeomb. Usually, multi-objective optimization design is used to obtain Pareto sets of optimal graded honeycomb. According to different application environment of graded honeycomb, appropriate graded honeycombs can be selected. The regular hexagonal honeycomb is taken as the research object in this paper, and the homogeneous honeycomb is divided into 4 layers for next optimal design. That the graded honeycomb recommended by the NSGA-I algorithm is compared with the homogeneous honeycomb. The results show that the graded honeycomb can greatly improve the initial peak force (P,PCF) while slightly inereasing the total energy absorption (E,EA) and specific energy absorption (S,SEA), and the maximum improvement is 78. 51 %, which proves the advantage of using this method for gradient design.